Correction to "Conformational Dynamics of the Nicotinic Acetylcholine Receptor Channel: A 35-ns Molecular Dynamics Simulation Study" - Xu, Yechun (2015)
The nicotinic acetylcholine receptor (AChR) is the paradigm of ligand-gated ion channels, integral membrane proteins that mediate fast intercellular communication in response to neurotransmitters. A 35-ns molecular dynamics simulation has been performed to explore the conformational dynamics of the entireme membrane-spanning region, including the ion channel pore of the AChR. In the simulation, the 20 transmembrane (TM) segments that comprise the whole TM domain of the receptor were inserted into a large dipalmitoylphosphatidylcholine (DPPC) bilayer. The dynamic behavior of individual TM segments and their corresponding AChR subunit helix bundles was examined in order to assess the contribution of each to the conformational transitions of the whole channel. Asymmetrical and asynchronous motions of the M1-M3 TM segments of each subunit were revealed. In addition, the outermost ring of five M4 TM helices was found to convey the effects exerted by the lipid molecules to the central channel domain. Remarkably, a closed-to-open conformational shift was found to occur in one of the channel ring positions in the time scale of the present simulations, the possible physiological significance of which is discussed.